PENGARUH KECERDASAN BUATAN TERHADAP KEMAMPUAN BERFIKIR KRITIS MELALUI AI LITERACY MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN DI UNIVERSITAS NEGERI SURABAYA - Nur Aini, Intan; Farida Panduwinata, Lifa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of artificial intelligence (AI) has made learning easier, but it also has the potential to reduce critical thinking ability if it is not used alongside adequate AI literacy. This study aims to analyse the influence of AI trust and AI attitude on critical thinking ability through AI literacy among students of the Office Administration Education Programme at the State University of Surabaya. The study used a quantitative approach with an explanatory research design. The study population consisted of 815 students from the 2022–2024 intake, with 268 respondents being selected using purposive sampling. Data were collected by distributing a questionnaire using a Likert scale and analysed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method with the help of SmartPLS. The results of the study show that AI trust and AI attitude have a positive and significant influence on critical thinking and AI literacy. AI Literacy was also found to have a positive and significant effect on critical thinking skills, and was found to mediate the influence of AI Trust and AI Attitude on critical thinking skills among students. The findings of this study show that critical thinking ability is not only influenced by the level of trust and attitude towards AI, but also by the ability to understand, evaluate, and use AI critically. Therefore, strengthening AI literacy is important in supporting the optimal use of AI to enhance students' critical thinking skills.